Detection of alloantigens during preimplantation development and early trophoblast differentiation in the mouse by immunoperoxidase labeling. - Searle, R F; Sellens, M H; Elson, J; Jenkinson, E J; Billington, W D (J Exp Med, 1976)
An immunoperoxidase-labeling technique allowing visualization of antibody binding to the cell surface at the electron microscopical level has been employed an an analysis of H-2 and non-H-2 alloantigen expression on the early mouse embryo. The presence of non-H-2 antigenic determinants has been confirmed on eight-cell, morula, and blastocyst stages of development. Contrary to previous reports, however, low levels of H-2 antigen have also been detected on the blastocyst. This is the earliest stage at which H-2 has been shown to be expressed on the fertilized mouse egg and may reflect the greater resolution of the immunoperoxidase technique. Using two different models to study the critical peri-implantation stages, those of experimentally induced blastocyst activation and blastocyst outgrowth in vitro, it has been demonstrated that antigen loss occurs on the trophectoderm at the time of implantation, and that this is not necessarily dependent upon maternal influence. It is suggested that the loss may be an important factor in the prevention of maternal immune rejection during the establishment of the fetal allograft. The two major components of the early postimplantation conceptus display a striking differential in antigenic status. The embryonic sac shows a high degree of peroxidase labeling, while the ectoplacental cone trophoblast is unlabeled. These findings add support to the concept of antigenic neutrality of the early trophoblast and its role in the maintenance of a normal fetomaternal immunological equilibrium.
Keywords: Animals; Binding Sites, Antibody; Blastocyst; Cell Differentiation; Cell Membrane; Embryo Implantation; Embryonic Development; Epitopes; Female; Histocompatibility Antigens; HLA Antigens; Horseradish Peroxidase; Mice; Mice, Inbred Strains; Pregnancy; Pregnancy, Animal; Trophoblasts